Acute kidney injury in China: a cross-sectional survey - Yang, Li; Xing, Guolan; Wang, Li; Wu, Yonggui; Li, Suhua; Xu, Gang; He, Qiang; Chen, Jianghua; Chen, Menghua; Liu, Xiaohua; Zhu, Zaizhi; Yang, Lin; et al. (The Lancet (British edition), 2015)
Acute kidney injury (AKI) has become a worldwide public health problem, but little information is available about the disease burden in China. We aimed to evaluate the burden of AKI and assess the availability of diagnosis and treatment in China. We launched a nationwide, cross-sectional survey of adult patients who were admitted to hospital in 2013 in academic or local hospitals from 22 provinces in mainland China. Patients with suspected AKI were screened out on the basis of changes in serum creatinine by the Laboratory Information System, and we reviewed medical records for 2 months (January and July) to confirm diagnoses. We assessed rates of AKI according to two identification criteria: the 2012 Kidney Disease: Improving Global Outcomes (KDIGO) AKI definition and an increase or decrease in serum creatinine by 50% during hospital stay (expanded criteria). We estimated national rates with data from the 2013 report by the Chinese National Health and Family Planning Commission and National Bureau of Statistics. Of 2 223 230 patients admitted to the 44 hospitals screened in 2013, 154 950 (7·0%) were suspected of having AKI by electronic screening, of whom 26 086 patients (from 374 286 total admissions) were reviewed with medical records to confirm the diagnosis of AKI. The detection rate of AKI was 0·99% (3687 of 374 286) by KDIGO criteria and 2·03% (7604 of 374 286) by expanded criteria, from which we estimate that 1·4–2·9 million people with AKI were admitted to hospital in China in 2013. The non-recognition rate of AKI was 74·2% (5608 of 7555 with available data). Renal referral was done in 21·4% (1625 of 7604) of the AKI cases, and renal replacement therapy was done in 59·3% (531 of 896) of those who had the indications. Delayed AKI recognition was an independent risk factor for in-hospital mortality, and renal referral was an independent protective factor for AKI under-recognition and mortality AKI has become a huge medical burden in China, with substantial underdiagnosis and undertreatment. Nephrologists should take the responsibility for leading the battle against AKI. National 985 Project of China, National Natural Science Foundation of China, Beijing Training Program for Talents, International Society of Nephrology Research Committee, and Bethune Fund Management Committee.